NDST1 missense mutations in autosomal recessive intellectual disability. Issue 11 (14th August 2014) - Reuter, Miriam S.; Musante, Luciana; Hu, Hao; Diederich, Stefan; Sticht, Heinrich; Ekici, Arif B.; Uebe, Steffen; Wienker, Thomas F.; Bartsch, Oliver; Zechner, Ulrich; Oppitz, Cornelia; Keleman, Krystyna; et al.
<x xml:space="preserve">Abstract</x> NDST1 was recently proposed as a candidate gene for autosomal recessive intellectual disability in two families. It encodes a bifunctional GlcNAc N‐deacetylase/N‐sulfotransferase with important functions in heparan sulfate biosynthesis. In mice, Ndst1 is crucial for embryonic development and homozygous null mutations are perinatally lethal. We now report on two additional unrelated families with homozygous missense NDST1 mutations. All mutations described to date predict the substitution of conserved amino acids in the sulfotransferase domain, and mutation modeling predicts drastic alterations in the local protein conformation. Comparing the four families, we noticed significant overlap in the clinical features, including both demonstrated and apparent intellectual disability, muscular hypotonia, epilepsy, and postnatal growth deficiency. Furthermore, in Drosophila, knockdown of sulfateless, the NDST ortholog, impairs long‐term memory, highlighting its function in cognition. Our data confirm NDST1 mutations as a cause of autosomal recessive intellectual disability with a distinctive phenotype, and support an important function of NDST1 in human development. © 2014 Wiley Periodicals, Inc.